The Swiss STAR trial – an evaluation of target groups for sexually transmitted infection screening in the sub-sample of men (Swiss Medical Weekly, 2020)
OBJECTIVES In Switzerland, universal health insurance does not cover any routine testing for sexually transmitted infections (STIs), not even in individuals at high risk, and extra-genital swabbing is not standard of care. We determined the prevalence and incidence of human immunodeficiency virus (HIV), viral hepatitis and non-viral STIs in a multicentre prospective observational cohort of multi-partner men who have sex with men (MSM) and other men. MATERIALS AND METHODS Between January 2016 and June 2017, we offered free STI testing to all men with multiple sexual partners (three or more in the previous 12 months), with follow-up examinations every 6 months. We used multiplex polymerase chain-reaction testing (for Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium) on pooled swabs (pharynx, urethra/vagina, anus), and antibody tests for HIV and Treponema pallidum at every visit, and for hepatitis B/C at baseline. RESULTS We screened 779 multi-partner MSM and 92 other men. Previously undiagnosed HIV was found in 0.5% vs 0.0%, respectively and T. pallidum antibodies in 15.3% vs 1.1%. STIs requiring antibiotic treatment comprised: active syphilis 1.7% vs 0.0%; N. gonorrhoeae 10.3% vs 0.0%; C. trachomatis 8.7% vs 1.1%. One in four MSM versus 1 in 100 other multi-partner men had any of these three STIs at baseline. 10.4% vs 1.3% had a history of hepatitis B, 31.9% vs 47.3% had no immunity (HBs-AB 20). CONCLUSION Among MSM, but not among other multi-partner men, STIs, mostly asymptomatic, are common. Given the high risk of onward transmission, low-cost or free routine screening of multi-partner MSM is a public health priority.